(untitled) (Huellas, 2026)
Ideas surrounding development and rural extension have a shared history of several decades in Latin America. The link between the two concepts stems from the fact that almost at the same time as development discourses began to guide Latin American public policy, rural extension has been considered as a tool for intervention in the most disadvantaged rural areas. This paper aims to systematize and analyze one of the public policies implemented by INTA under the guidelines of the Rural Territorial Development paradigm. The analysis focuses on the rural extension practice carried out during the implementation of Regional Projects with a Territorial Focus—between 2012 and 2018—and its capacity to generate transformations in the territories.